Implementasi Dan Kepatuhan Terhadap Peraturan Pemerintah Tentang Jaminan Kehilangan Pekerjaan (PP No. 6 Tahun 2025) - Fransinta Dewi Ayu; Galuh Regita Cahyani; Kafka Septiana; Tegar Harbriana Putra (Journal of Innovative and Creativity, 2025)
Termination of employment constitutes a major risk in industrial relations and directly affects workers’ livelihoods. The state has a constitutional obligation to provide legal and social protection for workers who lose their jobs. One such form of protection is the Job Loss Insurance (Jaminan Kehilangan Pekerjaan/JKP) program regulated under Government Regulation Number 6 of 2025. This study aims to analyze the regulation of JKP from the perspectives of legal protection and legal certainty, as well as to examine its implementation and the level of compliance by employers and the Employment Social Security Agency (BPJS Ketenagakerjaan). This research employs a normative juridical method with a qualitative approach, utilizing primary, secondary, and tertiary legal materials. The findings indicate that, normatively, Government Regulation No. 6 of 2025 reflects the principles of legal protection through both preventive and repressive mechanisms and aligns with the welfare state concept and social security theory. However, in terms of legal certainty, there remain normative inconsistencies with other labor-related regulations, particularly concerning post-termination rights and claim verification mechanisms. Furthermore, the implementation of JKP faces practical challenges, including low employer compliance, limited socialization, and institutional constraints within BPJS Ketenagakerjaan. These issues hinder the optimal fulfillment of workers’ rights. Therefore, regulatory harmonization, strengthened supervision, and improved legal literacy are essential to ensure the effective functioning of JKP as a post-termination worker protection instrument.